Peranan Kepala Sekolah Dan Guru Dalam Manajemen Kesiswaan Di SDK Santa Maria Ratu Rosari Gianyar - Wulandari, Dewa Ayu Riska; Prawita, Wayan Cahya; Sepriani, Ni Kadek (Jayapangus Press, 2023)
The principal is a role model who must be able to improve the quality of the school in carrying out the student management function which includes students, teachers and school physics, in the management of student management it is the most important thing to make optimal student conditions so that schools have quality, student management, school principals have a very significant and very basic role, starting from the admission of new students, student development or self-development to the student graduation process. The purpose of this study is to describe the role of the principal and teacher in student management at SDK Santa Maria Ratu Rosari Gianyar. This study used descriptive qualitative method. The data were taken by means of interviews, observation and documentation studies. In this study, the subjects of this study were the principal, vice principal for curriculum and student affairs, as well as several students and teachers in the field of study and administrative staff at this school. Based on the results of research and data analysis and conclusions, it was found that; 1) the principal has a function that greatly influences the development of the school, both school progress, student achievement and student character development. The ongoing student management process is in accordance with the plans previously prepared by the school in accordance with technical instructions from the education office. 2. Student management management of SD Santa Maria Ratu Rosari Gianyar is managed by student teachers, classroom teachers and education staff who have been appointed by the principal with the principal as the person in charge. The management of student management itself begins with planning for new student admissions by adjusting the capacity previously adapted to existing infrastructure and existing teachers and education personnel, then admitting new students, organizing students, student orientation, student coaching and service, and student assessment.